Addressing High-Level Discourse Units beyond the Paragraph: Challenges, Approaches and Materials - Salameh Jiménez, Shima; Pardo Llibrer, Adrià (Círculo de Lingüística Aplicada a la Comunicación, 2024)
Interest in the segmentation of written discourse has significantly increased in recent years. This phenomenon can be attributed to different factors, such as theorization (e.g., clear categorizations and delineation of units employed in written texts segmentation without relying on traditional syntax, the lack of consensus on the properties behind basic units like paragraph, etc.), didactics (e.g., the growing difficulty in writing formal texts, which has been observed in inadequate textual organization and information distribution, improper use of punctuation and discourse markers, etc.) and the emergence of new hybrid genres where units such as sentences or paragraphs may not completely align with the analyzed linguistic production (e.g., written texts on social media where there is no correspondence between a paragraph and a unit of meaning, or where even classical posticions such as initial, medial or final could be altered). Compared to segmentation models of oral discourse, widely developed (Pons, 2014), written discourse models seem to remain in the background despite their theoretical strength. This seems to be the result of an overshadowing derived from the interest in analyzing genres like colloquial conversation or interview. This special issue, composed of five papers based on different theoretical frameworks, aims to shed light on a key issue: organizing, characterizing, and delimiting units above paragraph and below the text, a challenging space for researchers.
Keywords: discourse segmentation; writing; paragraph; high-level units